PENGARUH MODEL COOPERATIVE LEARNING TIPE STUDENT TEAMS ACHIEVMENT DIVISION (STAD) TERHADAP KEMAMPUAN MENYIMAK PESERTA DIDIK SEKOLAH DASAR - Ahmad Sheca Rahmadi; Mega Diana, Siska; Kembar Habibi, Roy; Destini, Frida (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The problem in this research was the low listening ability of fourth-grade students in Indonesian language learning at SD Negeri 26 Tulang Bawang Tengah, which had not yet reached the Learning Objective Achievement Criteria (KKTP). This research aimed to determine the effect of the Cooperative Learning model of the Student Teams Achievement Division (STAD) type on the listening ability of fourth-grade elementary school students. The research method used was a quasi-experimental design with a non-equivalent control group design. The population in this research consisted of 70 students, while the sample consisted of 46 students, including 23 students in the experimental class and 23 students in the control class. The data collection techniques were conducted through pre-test and post-test, observation, and documentation. The data analysis used normality tests, homogeneity tests, N-gain tests, and simple linear regression tests.The results of the research showed that the Cooperative Learning model of the Student Teams Achievement Division (STAD) type affected the listening ability of fourth-grade students in Indonesian language learning at SD Negeri 26 Tulang Bawang Tengah.